A long-haul change : differential object marking in early Slavonic - Eckhoff, H (Journal of Historical Syntax, 2022)
This article uses extensive treebank data from the PROIEL and TOROT treebanks to track the much-debated rise of the animacy category in Russian, which in this article will be analysed as a change from at least partly definiteness-driven differential object marking in Old Church Slavonic via constructionally-conditioned variation in Old East Slavonic to fully fledged animacy subgender marking in late Middle Russian. The change is interest-ing from a methodological point of view as well, since it requires us to anno-tate data through an ongoing change, and also since conventional treebank annotation is not enough to capture the conditions of the observed variation and change: annotation for semantics and information structure is necessary too. The article describes and defends a conservative approach to annotation in the face of change: the analysis that fits the first attested stage of a change is retained as long as possible.